Influence of silver nanoparticles morphologies on density, viscosity and thermal conductivity of silver nanofluids and silver ionanofluids - Patil, Virendra Sudam; Andry, Cera-Manjarres; Salavera, Daniel; Rode, Chandrashekhar Vasant; Patil, Kashinath R; Coronas, Alberto (Journal of Nanofluids, 2018)
This paper explores the consequence of silver nanoparticles morphology (nanowires, nanoplates, and nanospheres) on density, viscosity and thermal conductivity of nanofluids and IoNanoFluids. Nuclear magnetic resonance spectroscopy results reveal that hydroxyl group in cation relates to silver nanoparticle surface of silver IoNanoFluid. Effect on bonding of silver nanoparticles after solvation in an ionic liquid was investigated with Infrared spectroscopy. UV-Visible spectroscopy analysis observed variations in color and optical properties of silver IoNanoFluids compared with nanofluids. Structural and morphological characterization of silver nanofluids and silver IoNanoFluids were carried out with Scanning electron microscopy and Transmission electron microscopy techniques. The presence of silver nanoparticles from the aqueous phase of nanofluids to viscous ionic liquid phase was confirmed by X-ray photoelectron spectroscopy and Energy dispersive analysis. The thermal stability study unveils that Choline bis(trifluromethylsulfonyl)imide ionic liquid, and its derived silver IoNanoFluids, are more stable than silver nanofluids. There was no considerable impact was observed for the silver nanoparticles morphology on the density of IoNanofluids. Moreover, two-dimensional silver structures raise the viscosity further compare to other two morphologies of silver nanoparticles in a base ionic liquid. Among all three studied morphologies, silver nanowires influence additional in the enhancement of thermal conductivity for silver nanofluids and IoNanoFluids. Enhanced thermal conductivity and reduced viscosity of silver nanowires based IoNanoFluid sorts this fluid as a potential heat transfer fluid.